The extent of application of the responsibility accounting system and its role in evaluating performance: an analytical research - Mehdi Attia Mohi; Jassim Mohammed Hussein (Iraqi Journal for Administrative Sciences, 2024)
The goal is to demonstrate the importance of applying the accounting responsibility system in organizations health service. The research problem is determined see whether administrative regulations, and procedures work going properly agreed with the elements of accounting responsibility by dividing the organization into sub-units and the importance of research stems from the importance of the subject, which dealt with the concept of responsibility accounting system and the extent of its application in health services organizations, and is based on the head of research hypothesis is: responsibility Accounting system does not contribute through its components in evaluating the performance of health services organizations,, using standard analytical approach. The research has come to a group of the most important conclusions that the accounting responsibility system helps management in evaluating the actual performance of the center of the cost and responsibility to determine deviations and processed, has been to reach a need to emphasize the application of accounting responsibility system through proper and thoughtful scientific bases, especially in terms of planning, control and performance evaluation processes .